2023
DOI: 10.3390/su151310339
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Bioelectricity Generation Using Lettuce Waste as Substrate by Microbial Fuel Cells

Abstract: Agricultural waste negatively impacts the environment and generates economic difficulties for agro-industrial companies and farmers. As a result, it is necessary for an eco-friendly and sustainable alternative to managing this type of waste. Therefore, the research aimed to investigate lettuce waste as an alternative substrate to generate bioelectricity in single-chamber microbial fuel cells (scMFCs). It was possible to report voltage and electric current peaks of 0.959 ± 0.026 V and 5.697 ± 0.065 mA on the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…The values of the electric current decrease when the organic matter is depleted because the microbes lose their nutrients to carry out their metabolism and release electrons to the medium [38]. Lettuce waste has been reported as substrates in MFCs, generating electrical current peaks of 5.697 ± 0.065 mA, mentioning that the corrosion of the metal electrodes in the last days of the operation of the MFCs influenced the decrease in its current values [39]. Abubakar et al (2023) reported that the absence or low concentration of exoelectrogenic microbes or other types of microorganisms with high concentrations of organic matter leads to the low efficiency of the MFCs, and the absence of microorganisms is due to the inadequate choice of the standardization of the pH value during the operation of the MFCs [40].…”
Section: Results and Analysismentioning
confidence: 99%
“…The values of the electric current decrease when the organic matter is depleted because the microbes lose their nutrients to carry out their metabolism and release electrons to the medium [38]. Lettuce waste has been reported as substrates in MFCs, generating electrical current peaks of 5.697 ± 0.065 mA, mentioning that the corrosion of the metal electrodes in the last days of the operation of the MFCs influenced the decrease in its current values [39]. Abubakar et al (2023) reported that the absence or low concentration of exoelectrogenic microbes or other types of microorganisms with high concentrations of organic matter leads to the low efficiency of the MFCs, and the absence of microorganisms is due to the inadequate choice of the standardization of the pH value during the operation of the MFCs [40].…”
Section: Results and Analysismentioning
confidence: 99%
“…In the following days, the values experienced a gradual decrease until they produced 1.93 mA on day 30. The peak current values shown in the first days are attributed to the good formation of the electrogenic biofilm [46], which depends largely on the measurement of the carbon sources present in the substrates [47], which act as an energy supply in the biological process of microorganisms to produce electric current [48]. As the organic compounds decrease, the production of electrons is reduced, thus generating a lower electrical current in the last few days [49].…”
Section: Measurement Of Electrochemical Parameters Of Mfcsmentioning
confidence: 99%
“…Currently, the large scientific community has begun to use different types of waste as fuel, but in recent years, agricultural waste has become relevant for its use as fuel. Recently, Rojas-Villacorta et al (2023) reported that using vegetable waste, for example lettuce, as a substrate in MFCs and Cu and Zn electrodes can generate current and voltage values of 5.697 ± 0.065 mA and 0.959 ± 0.026 V [20]. Likewise, Aleid et al ( 2023) used fruit waste mixtures as fuel, generating peaks of 0.125 V on day 25 in their single-chamber MFCs with graphite electrodes [21].…”
Section: Introductionmentioning
confidence: 99%